Impact of homocysteine levels on clinical outcome in patients with acute ischemic stroke receiving intravenous thrombolysis therapy - Li, Lei (PeerJ, 2020)
BACKGROUND: The purpose of this study was to retrospectively assess the potential correlation between clinical outcomes and homocysteine (Hcy) levels in acute ischemic stroke (AIS) patients after recombinant tissue plasminogen activator (rtPA) treatment. METHODS: AIS patients treated by rtPA were enrolled between September 2018 and March 2019 in the Stroke Center (Department of Neurology and Neurosurgery), Shanghai Tenth People’s Hospital, Tongji University School of Medicine. Demographics, baseline and clinical characteristics, and modified Rankin Scale (mRS) score after three months from the onset were retrospectively analyzed. Then we compared data about demographics, baseline and clinical characteristics between patients with favorable (mRS score 0–2) and unfavorable (mRS score 3–6) outcomes. RESULTS: Among 141 patients, 36 patients had poor outcome, for an incidence of 25.53%. Univariate analysis showed that higher Hcy levels (OR = 1.07, 95% CI [1.02–1.12]), older age (OR = 1.06, 95% CI [1.02–1.10]), longer door to needle time (DNT) (OR = 1.03, 95% CI [1.01–1.05]), higher D-Dimer levels (OR = 1.33, 95% CI [1.03–1.71]), and higher National Institutes of Health Stroke Scale (NIHSS) score before treatment (OR = 1.21, 95% CI [1.08–1.35]) were each associated with poor outcome. Also, without internal carotid artery plaque (OR = 0.30, 95% CI [0.10–0.92]) showed a protective effect on patients’ clinical outcome. Patients with higher levels of Hcy decline also showed an increased risk of poor outcome for AIS patients obtaining rtPA treatment (Non-adjusted: OR = 1.07, 95% CI [1.02–1.12]; Adjust model I adjusts for demographics (age, male): OR = 1.06, 95% CI [1.02–1.11]; Adjust model II adjusts for hospital care factors (onset to treatment, DNT): OR = 1.08, 95% CI [1.03–1.13]; Adjust model III adjusts for health and stroke factors (INR, D-Dimer, HGB, NIHSS score before treatment, smoking, drinking, hypertension, diabetes, coronary disease, hyperlipidemia, previous stroke, atrial fibrillation, hemorrhagic transformation, internal carotid artery plaque): OR = 1.06, 95% CI [1.02–1.11]). The results are very stable in all three models constructed. CONCLUSION: The results of this study indicate that increased Hcy level independently predicts unfavorable outcome in AIS patients accepting thrombolytic therapy. However, the contribution of Hcy to the outcome, although significant, is relatively small and perhaps not clinically significant when all the other confounders are considered.